Lunar rhythms in growth of larval fish. Issue 1942 (13th January 2021) - Shima, Jeffrey S.; Osenberg, Craig W.; Noonburg, Erik G.; Alonzo, Suzanne H.; Swearer, Stephen E.
Abstract : Growth and survival of larval fishes is highly variable and unpredictable. Our limited understanding of this variation constrains our ability to forecast population dynamics and effectively manage fisheries. Here we show that daily growth rates of a coral reef fish (the sixbar wrasse, Thalassoma hardwicke ) are strongly lunar-periodic and predicted by the timing of nocturnal brightness: growth was maximized when the first half of the night was dark and the second half of the night was bright. Cloud cover that obscured moonlight facilitated a 'natural experiment', and confirmed the effect of moonlight on growth. We suggest that lunar-periodic growth may be attributable to light-mediated suppression of diel vertical migrations of predators and prey. Accounting for such effects will improve our capacity to predict the future dynamics of marine populations, especially in response to climate-driven changes in nocturnal cloud cover and intensification of artificial light, which could lead to population declines by reducing larval survival and growth.